Density and Porosity Analysis of Limestone as a Groundwater Reservoir in Kayubulan Village, Gorontalo Regency - Ahmad, Fadhil Abdillah; Permana, Aang Panji; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2025)
This study examines the potential of limestone in Kayubulan Village, Batudaa Pantai District, Gorontalo Regency, to determine its suitability as a groundwater reservoir. The research focuses on understanding the relationship between rock density and porosity, which are key factors in water storage capacity. The methods employed include geological field mapping, specific gravity testing following SNI 1969:2008 standards, and petrographic analysis. Geological field mapping identified the distribution and characteristics of limestone facies, while specific gravity testing involved measuring dry weight (ð‘Šâ‚€) and saturated weight (W_w),which were incorporated into Giancoli's (2014) density formula. Petrographic analysis was conducted to examine the inverse relationship between density and porosity in various limestone facies and to identify porosity types.Five samples representing Wackestone, Packstone, Crystalline Carbonate, and Coralline Framestone facies were analyzed for density, porosity, and water absorption. Based on Koesoemadinata's (1980) classification, porosity values were as follows: Wackestone 4.49% (negligible), Packstone 8.4% (poor), Wackestone FAK 12 10.54% (fair), Crystalline Carbonate 12.69% (good), and Coralline Framestone 23.7% (very good). Variations in micrite and sparite composition also influenced porosity; Wackestone FAK 15 showed lower porosity than FAK 12 due to its higher sparite content.Coralline Framestone emerged as the most viable reservoir candidate, as high-porosity, low-density rocks generally exhibit superior water absorption capacities. These findings highlight the significance of porosity and density in groundwater management and offer valuable insights for optimizing Gorontalo's water resources.